Fatigue Performance and Fatigue Life Prediction for RV-20E Reducers Based on the Crankshaft Heat Treatment Strengthening Process - Zhu Qingwang; Zhang Jing; Dai Yanran (Jixie chuandong)
Fatigue performance of RV-20E reducers is investigated experimentally herein; load and life curves of RV-20E with different crankshaft heat treatment strengthening processes are obtained. The optimum surface microstructure and optimum surface hardness of the crankshaft for improving the fatigue life of the RV-20E reducer are analyzed, and the failure mode and failure mechanism of the crankshaft of the RV-20E reducer are discussed. Based on the S-N theory and the Miner theory, and combined with the force analysis of RV-20E, the life parameter of RV-20E reducers based on the crankshaft needle roller bearing assembly is derived, and the test data is compared and analyzed. The analysis and comparison show that the life parameter can effectively correlate the fatigue life of RV-20E reducers and can be used to predict the fatigue life of RV-20E reducers.